PENGARUH WAKTU PEMBERIAN DAN DOSIS PUPUK NPK PELANGI TERHADAP PERTUMBUHAN TANAMAN JAGUNG MANIS VARIETAS SWEET BOYS (Zea Mays Saccharata Sturt) - Suntoro dan Puji Astuti (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Effect Of Application Time and NPK Fertilizer Dosage on The Growth of Sweet Corn (Zea Mays Saccharata Sturt), Sweet Boys Variety.  Research objectives: 1. To determine the effect of time and dose of NPK fertilizer and their interaction on the growth of rainbow corn crop. 2. Time and dose of NPK fertilizer on the growth of rainbow sweet corn is a good crop.The research was conducted in a randomized completc block design arranged (RCBD) with a 2 x 4 factorial analysis and repeated twice. The first factor when fertilizer (W) consists of three levels namely: w1 = initial planting, w2 = one month after planting. The second factor fertilizer NPK Pelangi (K) consists of four levels: k0 = Without NPK fertilizer (control), k1 = 61.2 g plot -1 equivalent to 100 g ha -1, k2 = 122.4 g plot -1 equivalent with 200 g ha -1, k3 = 183.6 g plot -1 ha -1 equivalenltol300g.Timing of fertilizer treatment (W) gives no real effect on the average height of plant age 15 days, 30 days, age at exit female flowers, male flowers, cob girth, wet production and production of the fruit cob cob without cornhusk but highly significant the plant height 45 days, ear length. Average yield of cobs without klobot wet weight was obtained on treatment w1 (NPK fertilizer rainbow After onelmonthloflplanting)lofl6.77ltonneslha-1. Treatment NPK Pelangi (K) highly significant effect on plant height age of 30.40 days, ear length, ear diameter, fresh weight of the fruit without klobot cobs and cobs without klobot production. Average yield wet weight cob without klobot obtained at treatment NPK rainbow k3 (183.6 mg plot-1) of 6.77 tonnes ha-1. Treatment interaction (WxK) and NPK rainbow tillage were not significantly different in all the observed variables.